Farmers’ Voices: Concerns within the Agricultural Advertiser-Media-Reader Triad - Stephen A. Banning; James F. Evans (Journal of Applied Communications, 2004)
This study continues an examination of power relationships within the agricultural publishing triad: advertisers, periodicals, and producer readers. It focuses on the views of farmers about the farm periodicals they read and the agricultural marketers that advertise in those periodicals. A mail survey was used to learn the opinions and observations of farmers in a nationwide sample. The sample of 497 was randomly drawn from a government database by a commercial data supply service. Three waves of letters were used along with a 1 incentive. The 198 completed responses came from 29 states. Results indicate that producers are quite discerning and insightful in what they read. Furthermore, a majority expressed concern about advertiser-editorial relationships. Most said they see evidence of advertiser influence in the form of editorial trade-offs and bias in what stories are covered (or not covered) and how topics are handled. Results of a credibility index indicate there is much room for improvement. Authors suggest that farm publishers and advertisers should reconsider their relationships if they wish to address readers’ concerns and improve their credibility. In a highly competitive environment, increased credibility has positive bottom-line implications for all partners in the triad.